Performance of BAZNAS Empowerment Program in Indonesia: A Systematic Literature Review - Khatimah, Husnul; Beik, Irfan Syauqi; Nuradi, Nuradi (Prosperity: Journal of Society and Empowerment, 2024)
This study aims to determine how the development of research topics related to the performance of the BAZNAS mustahik empowerment program in the last 5 years. The research method used is a qualitative method with a Systematic Literature Review (SLR) approach using the VOSviewer application on journal papers indexed by Scopus and Google Scholar and published from 2019-2024. The results showed that research interest in BAZNAS empowerment programs has increased over the past 5 years. BAZNAS, in terms of institutions, has a very good performance in carrying out mustahik economic empowerment programs through business capital assistance and not only providing guidance in terms of material but also the spiritual side by running mosque-based programs and collaborating with da'i and Islamic universities as evidenced by the condition of mustahik who have begun to turn into muktafi and munfiq which shows that in Islam there is the concept of abundance, there is a sense of wanting to share despite limitations. However, the obstacles come from the mustahik themselves because their low level of education affects their mindset to change for the better, in addition to the limited human resources of assistants who have not been able to maximize training and coaching.